Handbook of human resource development - Chalofsky, Neal, 1945-; Rocco, Tonette S., 1954-; Morris, Michael Lane, 1959- (San Francisco, CA : Wiley, 2014)
'The handbook features 42 chapters authored/co-authored by 62 authoritative academic and scholar-practitioners (chapter summaries and contributor bios are available):1. HRD - The Profession and the Discipline - Neal Chalofsky2. Foundations of the discipline of HRD 3. Issues & Perspectives on HRD4. Philosophy and Values of HRD 5. Managing the Workforce 6. Management and HRD 7. Innovative Applications 8. Future Directions'--
Includes indexes.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Personnel management; Career development; Manpower planning; Electronic books; Electronic books